2013
DOI: 10.1371/journal.pgen.1003950
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the Murine Cytochrome P450 Cyp2j Locus by Fused BAC-Mediated Recombination Identifies a Role for Cyp2j in the Pulmonary Vascular Response to Hypoxia

Abstract: Epoxyeicosatrienoic acids (EETs) confer vasoactive and cardioprotective functions. Genetic analysis of the contributions of these short-lived mediators to pathophysiology has been confounded to date by the allelic expansion in rodents of the portion of the genome syntenic to human CYP2J2, a gene encoding one of the principle cytochrome P450 epoxygenases responsible for the formation of EETs in humans. Mice have eight potentially functional genes that could direct the synthesis of epoxygenases with properties s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 44 publications
(60 reference statements)
1
21
0
Order By: Relevance
“…The availability of novel gene-targeting techniques allowed us to determine the role of murine Cyp2j in the regulation of chronic pulmonary vascular responses to hypoxic exposure in mice. In a previous study, we demonstrated that Cyp2j-deficient mice exhibit impaired HPV (13). Based on these data, in the present study we hypothesized that Cyp2j deficiency would prevent the development of chronic PH and vascular remodeling during prolonged exposure to hypoxia.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…The availability of novel gene-targeting techniques allowed us to determine the role of murine Cyp2j in the regulation of chronic pulmonary vascular responses to hypoxic exposure in mice. In a previous study, we demonstrated that Cyp2j-deficient mice exhibit impaired HPV (13). Based on these data, in the present study we hypothesized that Cyp2j deficiency would prevent the development of chronic PH and vascular remodeling during prolonged exposure to hypoxia.…”
Section: Discussionmentioning
confidence: 55%
“…Alternatively, it is possible that cytochrome P450 epoxygenases other than Cyp2j can contribute to the development of PH in Cyp2j 2/2 mice. We have previously reported that Cyp2c genes are expressed in the lungs of Cyp2j 2/2 mice of both genders (13). We reported that pulmonary Cyp2c29 and Cyp2c38 mRNA levels did not differ between Cyp2j 1/1 and Cyp2j 2/2 mice breathing at FI O 2 0.21 (13).…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Human CYP2J2 epoxygenates AEA and 2-arachidonoylglycerol (2-AG) (28) and is physiologically relevant, because it is the second most highly expressed P450 in the human brain (29) and is the most highly expressed P450 in human cardiomyocytes (30). However, the cross-species studies are not completely translatable, because BV-2 microglial cells are derived from mice, which have 10 subfamily CYP2J isozymes (CYP2J-5, -6, -7, -8, -9, -11, -12, -13, -14, -15) but lack a comparable CYP2J2 isozyme, making comparative species studies more difficult (31). Importantly, we show that coincubation of BV-2 microglia with a broad inhibitor of CYP enzymes (ketoconazole) significantly reduces the levels of the EEQ-EA and EDP-EA regioisomers ( Fig.…”
Section: Resultsmentioning
confidence: 99%